(untitled) (Research, Society and Development, 2020)
Histoplasmosis is a systemic fungal disease, which can manifest with extrapulmonary lesions. Oral lesions are rarely the first manifestation of late histoplasmosis and can represent an important process of immune imbalance. The objective of this work is to present a clinical case of Histoplasmosis with an oral manifestation of a patient who was unaware of her condition with the Human Immunodeficiency Virus (HIV). The patient’s main complaint was a painful ulcer in the central region of the tongue present for two months, whose incisional biopsy resulted in the diagnosis of Histoplasmosis. Although referred for medical treatment with an infectologist, the patient had complications resulting from the disease and died after one month. This situation demonstrates the importance of multidisciplinary care in the prevention, diagnosis and treatment of diseases. The correct diagnosis and treatment can be decisive in the prognosis of patients and demonstrates the relevance of the dentist’s knowledge about the various systemic diseases that present oral manifestations.